THE EFFECTS OF GINKGO BILOBA LEAF EXTRACT ON METABOLIC DISTURBANCES ASSOCIATED TO ALLOXAN-INDUCED DIABETIC RATS - M. Naseem1; M. Q. Zaman; H. Nazih; K. Ouguerram; I. Rabbani; H. Zaneb; T. Yaqoob; H. U. Rehman; J. Michel; S. K. Tahir; M. S. Yousaf; K. A. Majeed; et al. (Journal of Animal and Plant Sciences, 2016)
Ginkgo biloba leaf extract (GBE) considered one of the most effective therapeutic herbs. We evaluated anti-diabetic activities of GBE in rats. Rats were fed highly-fat diet for two weeks and divided into three groups (n=8): Non-diabetic control group (CG), Diabetic group (DG), Diabetic+100mg/kg GBE group (D+GBE). On 14th day, the rats were kept in overnight-fasting and administered single intra-peritoneal injection of alloxan-monohydrate (120-130mg/Kg body weight (BW). BW and blood glucose were measured weekly up to 14th week. Fasting/basal blood samples were collected for the biochemical analyses. Liver, skeletal muscle and adipose tissue were also collected for mRNA gene expressions (GLUT-4, IRS-1, IR, PEPCK, SREBP-1c, FAS, PPAR-α, PPAR-γ, TNF-α). Significant reduction in BW was found in D+GBE group at week 14. Glycemia became normalized as an effect of treatment. GBE significantly decreased serum glucose, urea and ALT concentrations. We observed significant higher catalase and lower malondialdehyde levels in D+GBE group. GBE significantly increased HDL-Cholesterol and reduced triglycerides and VLDL-Triglycerides levels. GBE showed up-regulation for hepatic IRS-1 and down-regulation for PEPCK, however, up-regulation for GLUT-4 and PPAR-α found in muscle. Treatment decreased TNF-α expression in liver and adipose tissue. GBE has anti-diabetic mediated by a modulating effect on involved key genes.
Keywords: Alloxan; Carbohydrate and lipid metabolism; Diabetes mellitus; Ginkgo biloba leaf extract; Rats